Analisis Zakat sebagai Sumber Kekayaan Negara - Heni Noviarita; Syara Dwi Afiana; Leny Indahsari; Dwi Nurhayati (Penerbit Goodwood, 2022)
Indonesia has the largest Muslim population, where the value of receiving zakat in Indonesia should have enormous potential for the welfare of the people. This can be seen from the receipt of zakat from BAZNAS, LAZ and OPZ in 2019 reaching Rp. 10,227,943,806,555. This is what makes zakat has the potential as a source of state revenue. Purpose: Therefore, this study aims to determine the potential of zakat as state revenue as well as its management and distribution. Research Methodology: The research method used by researchers is a descriptive qualitative method with a type of literature study. Where data collection is obtained from various sources in the form of articles and journals related to the discussion. Result: The results of this study indicate that zakat zakat has the same goal as one of the goals of the state contained in the 1945 Constitution, namely advancing the welfare and prosperity of the people and reducing economic inequality. This is what makes the potential for receiving zakat as a source of state revenue. As for the management and distribution mechanism in including zakat as an instrument of state revenue, that can be done in two ways, namely by centralizing the collection or collection of zakat funds into the State Treasury Account which will then be budgeted in the APBN to be managed and distributed to mustahik according to Islamic law.